Accumation rates of manganese in pelagic sediments using Brunnes-Matuyama magnetic reversal boundary - Michael L Bender; Teh-Lung Ku; Wallace S Broecker (PANGAEA, 2022)
For 27 pelagic sediment cores, the Brunnes-Matuyama magnetic reversal boundary (700 000 yr) was used to establish the mean sedimentation rate between this level and the core top. If the tops of these cores were lost, calculated sedimentation rates would be a few percent less than the true rates. Because CaCO3 is a Mn-free diluent, the Mn concentration results and the sediment accumulation rate results are given on a carbonate-free basis. CaCO3 content of cores raised from below the carbonate compensation level is taken as zero. The in situ density of water-free deep-sea cores was assumed to be 0.7 g/cm^3 , this could lead in some cases to an error.
In: Bender, ML et al. (2022): Accumulation rates of manganese in pelagic sediments and nodules [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.949670